Robert Stenberg's Theory of Triangular Love in Colleen Hoover's All Your Perfects - Jovita Anugrah Santoso; Tri Pramesti (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This article focuses on An American author of romance and adult fiction, Colleen Hoover shares her ideas about love and marriage in her novel “All Your Perfects", first published in 2018. It is a profound novel that explores the complexities of love and relationships in a way that is both insightful and thought-provoking about a damaged couple whose potential future hinges on promises made in the past. Colleen Hoover depicts how Graham and Quinn, as the main characters, fall in love and later how they face obstacles that threaten to tear them apart after seven years of marriage. The purpose of this study is to describe how consummate love is depicted in the novel “All Your Perfects” by Colleen Hoover and the effects of consummate love experienced by the main characters. The writer used a psychological approach to discover the styles of consummate love in Robert Stenberg’s Theory Triangular of Love in the novel “All Your Perfects”. The writer uses the novel as the main data and several journals and articles about romantic love, marriage, relationship, and the concept of triangular love by Robert J Sternberg as supporting data. According to Robert Sternberg’s Theory Triangular of Love, the result of this thesis is that both characters in the novel, Quinn and Graham, have experienced depicted and the effects of consummate love style with three components of a relationship: intimacy, passion, and commitment.